Mutations of the Genomes Uncoupled 4 Gene Cause ROS Accumulation and Repress Expression of Peroxidase Genes in Rice - Li, Rui-Qing; Jiang, Meng; Huang, Jian-Zhong; Møller, Ian Max; Shu, Qing-Yao (Frontiers in Plant Science, 2021)
The Genomes Uncoupled 4 (GUN4) is one of the retrograde signaling genes in Arabidopsis and its orthologs have been identified in oxygenic phototrophic organisms from cyanobacterium to higher plants. GUN4 is involved in tetrapyrrole biosynthesis and its mutation often causes chlorophyll-deficient phenotypes with increased levels of reactive oxygen species (ROS), hence it has been speculated that GUN4 may also play a role in photoprotection. However, the biological mechanism leading to the increased ROS accumulation in gun4 mutants remains largely unknown. In our previous studies, we generated an epi-mutant allele of OsGUN4 (gun4epi), which downregulated its expression to ~0.5% that of its wildtype (WT), and a complete knockout allele gun4-1 due to abolishment of its translation start site. In the present study, three types of F2 plant derived from a gun4-1/gun4epi cross, i.e. gun4-1/gun4-1, gun4-1/gun4epi and gun4epi/gun4epi were developed and used for further investigation by growing them under photoperiodic condition (16 h/8 h light/dark) with low light (LL, 100 μmol photons m-2 s-1) and high light (HL, 1000 μmol photons m-2 s-1). The expression of OsGUN4 was light responsive and had two peaks in the daytime. gun4-1/gun4-1-F2 seeds showed defective germination and died within 7 days. Significantly higher levels of ROS accumulated in all types of OsGUN4 mutants than in WT plants under both the LL and HL conditions. A comparative RNA-seq analysis of WT variety LTB and its gun4epi mutant HYB led to the identification of eight peroxidase (PRX)-encoding genes that were significantly downregulated in HYB. The transcription of these eight PRX genes was restored in transgenic HYB protoplasts overexpressing OsGUN4, while their expression was repressed in LTB protoplasts transformed with an OsGUN4 silencing vector. We conclude that OsGUN4 is indispensable for rice, its expression is light- and oxidative-stress responsive, and it plays a role in ROS accumulation via its involvement in the transcriptional regulation of PRX genes. s